PRINSIP KESANTUNAN BERBAHASA DI LINGKUNGAN MASYARAKAT DESA BETUNG KECAMATAN PEMATANGSAWA KABUPATEN TANGGAMUS - Abdulloh Abdulloh (LPPM STKIP PGRI Bandar Lampung, 2019)
The purpose of this research is to find out and describe the application and deviations of politeness maxim maxim in the language of the Betung Pematangsawa community based on their maxims. The principle of politeness analyzed: maxim of wisdom, acceptance, generosity, humility, compatibility, conclusions. The method uses qualitative. The subject is the Betung Pematangsawa community. Data collection uses records and analyzed with qualitative analysis. The results showed that at the wisdom maxim, the speakers of the language showed sufficient application well. There are only a few that show deviations. At the reception maxim, the speakers of the discussion do not show much deviation. Speakers of language show better application in speech acts of discussion in the Betung community. In the maxim of generosity, its application has shown attitudes and speeches respecting the interlocutor. Only a few speeches that deviate. In humble maxims, language speakers in Betung citizens' discussion show maximal deviations because many express their opinions without regard to the opinions of their interlocutors. In the compatibility maxim, there are quite a lot that indicate compatibility or agreement because of the deliberations that are conducted to reach mutual agreement. In the maximal sympathy, there is less visible deviation but there are some that are considered deviant because of the strengths.